ANALISIS PERTUMBUHAN VARIETAS LOKAL DAN UNGGUL PADI SAWAH PADA BUDIDAYA SECARA ORGANIK - Achmad Fatchul Aziez (JURNAL ILMIAH AGRINECA, 2017)
Application of organic farming of rice in generally used local varieties, while improved varieties are rarely used. Local and improved varieties of rice have different agronomic characters so if growth will be different of organic culture. The purpose of this study was to analyze the growth of local and improved varieties of rice under organic culture. The experiment was conducted in irrigated soil with inceptisol, altitude 114 m asl in Kebonagung, Imogiri, Bantul. The design used was randomized completely block design factorial 2 factors was repeated 3 times. The first factor was the kinds of farming, i.e. organic farming and conventional farming and the second factor was the kinds of varieties of rice comprising 5 different varieties of rice which consisted of Mentikwangi, Pandanwangi and Cianjur as local varieties and IR64 and Cisedane as improved varieties. The parameters observed leaf area index (LAI), age of leaf area (ALA), specific leaf weight (SLW), net assimilation rate (NAR), relative growth rate (RGR), and crop growth rate (CGR). The results of this study show that (1) the increasing age of the plant, then the ratio of LAI, ALA, NAR, RGR, and CGR between organic and conventional farming has decreased, (2) NARÂ  there is a close relationship with the SLW, (3) RGR there is a close relationship with theÂ  ALA, SLW, and NAR, (4) CGR there is a close relationship with the SLW and NAR.